Chlorhexidine mouthwash as an adjunct to mechanical therapy in chronic periodontitis: A meta-analysis - da Costa, Luiz Fernando Noira Passos; Amaral, Cristine da Silva Furtado; Barbirato, Davi da Silva; Leão, Anna Thereza Thomé; Fogacci, Mariana Fampa (The Journal of the American Dental Association (1939), 2017)
Through a systematic literature review, the authors evaluated the use of chlorhexidine (CHX) mouthwash as an adjunct to mechanical periodontal therapy for chronic periodontitis. The authors performed a systematic search by using PubMed (MEDLINE), Scopus, Scientific Electronic Library Online, and Cochrane Central Register of Controlled Trials. The authors selected randomized controlled clinical trials in which the investigators evaluated the probing depth (PD) and clinical attachment level (CAL) in test groups by using CHX as an adjuvant and in control groups and subject to mechanical periodontal therapy (scaling and root planing [SRP] 4-6 visits or 24 hours). The literature search resulted in 8 articles, which the authors then assessed for quality. After testing for heterogeneity, the authors performed a meta-analysis only in the SRP group with 4 to 6 visits. Results were positive for both PD and CAL with use of CHX. However, the summary measure was significant (P < .05) only for PD at 40 to 60 days (0.33 millimeters; 95% confidence interval, 0.08 to 0.58 mm) and 180 days (0.24 mm; 95% confidence interval, 0.02 to 0.47 mm) of follow-up, showing positive results for the use of CHX at those times. Although those differences were statistically significant, they could be interpreted as clinically slight. Adjunctive use of CHX mouthrinse with mechanical SRP resulted in slightly greater PD reduction than did SRP alone. Clinicians must consider the small additional gain in PD reduction, negligible effect on CAL, and potential for tooth staining when using CHX as an adjunct to SRP in treating chronic periodontitis.